PEMBAPTISAN ADALAH PENGAKUAN DAN PEMAKLUMAN SEBAGAI MILIK KRITUS - Mahulae, Kristinus C. (LOGOS, 2003)
In the primitives they believed that certain waters can be impregnated with the power of deity. The rites of purifications tended to assume the character of rites of consecration or initiation. A gentile was unclean, and so could be admitted into Jewish communions with a tebilah, a ritual bath of purification. In Qumran Community and Essenes the lustrations were effective for the cleansing of moral impurity. One of them was John the Baptist. The baptism of John was a bath of purification for the coming of the Reign of God. The first christians proclaimed the gospel with joyous certainty. The response to that good news was called for in terms of repentance, faith and baptism. Baptism is an overt, public act that expresses inward decision and intent, since it is performed in the open, and not in secret, it becomes by its nature a confession of faith. The name of the Lord is called over the baptized, therefore he dedicates himself to the Lord and he is appropriated for Him.